'Lines in the sand': an Australian qualitative study of patient group practices to promote independence from pharmaceutical industry funders. Issue 2 (9th February 2021) - Parker, Lisa; Grundy, Quinn; Fabbri, Alice; Mintzes, Barbara; Bero, Lisa
Abstract : Objectives: To study how patient groups that accept pharmaceutical industry money perceive and manage the risk of undue influence from their sponsors. Design: Empirical ethics approach using a qualitative interview study. Setting: The Australian patient group sector. Participants: 27 participants from 23 patient groups, purposively recruited for diversity of group characteristics (degree of pharmaceutical industry funding, health focus, location) and participant role (staff, board members). Analysis: Interview data were transcribed and read repeatedly to identify concepts and patterns in the data. These were grouped into conceptual categories that described and explained the findings. We used an inductive analytical approach to identify important themes and concepts in the data. Results: Participants in this study described how the patient group sector receives pressure from pharmaceutical company funders to act in ways that prioritise company interests. Groups worked to try and protect their credibility and ability to act in ways of their own choosing using practical rules or 'lines in the sand' about industry funding activities. They were grouped around the dominant topics of: sponsor exclusivity, brand marketing, agenda setting, advocacy and content of group activities. Lines in the sand were largely experience-driven and ethically informed; they varied between groups. There was also variable transparency among groups about financial interactions with pharmaceutical companies. Conclusions: It is important to know about patient group practices around pharmaceutical industry funders as this allows public scrutiny about the adequacy of such practices. Inadequate strategies may mean that funders can influence patient groups activities in ways that do not necessarily prioritise the interests of members. We found that groups differed in their approach, with little independent external guidance to inform responses to commonly encountered types of influence. Inadequate transparency limits the ability of the public to make informed assessments about the risk of bias over the activities of groups that accept industry funding.